THE IMPORTANCE OF FINANCIAL CONTROL IN THE FINANCING OF SECONDARY SCHOOLS - Sharapova Mashkhura Azadovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article highlights the need for financing of general education institutions by the state, as well as various sources of financing of the education system and ways of their targeted use. At the same time, the emphasis is placed on the share of expenditures allocated to education in GDP, and on increasing the importance of financial control in the effective use of budget funds.